2'-O-methylation within bacterial RNA acts as suppressor of TLR7/TLR8 activation in human innate immune cells - Rimbach, Katharina; Kaiser, Steffen; Helm, Mark; Dalpke, Alexander; Eigenbrod, Tatjana (Journal of innate immunity, 2015)
Microbial RNA is an important stimulator of innate immune responses. Differences in posttranscriptional RNA modification profiles enable the immune system to discriminate between self and non-self nucleic acids. This principle may be exploited by certain bacteria to circumvent immune cell activation. In this regard, 2'-O-methylation of Escherichia coli tRNATyr at position 18 (Gm18) has recently been described to inhibit TLR7-mediated IFN-a production in human plasmacytoid dendritic cells (pDCs). Extending these findings, we now demonstrate that Gm18 also potently inhibits TLR7-independent human monocyte activation by RNA derived from a variety of bacterial strains. The half minimal inhibitory concentration values were similar to those found for IFN-a inhibition in pDCs. Mechanistically, 2'-O-methylated RNA impaired upstream signalling events, including MAP kinase and NFκB activation. Our results suggest that antagonizing effects of Gm18-modified RNA are due to competition with stimulatory RNA for receptor binding. The antagonistic effect was specific for RNA because the small molecule TLR7/8 agonist R848 was not inhibited. Despite the striking phenotype in human cells, 2'-O-methylated RNA did not interfere with TLR13 activation by bacterial 23S rRNA in murine DC and BMDM. Thus, we identify here Gm18 in E. coli tRNATyr as a universal suppressor of innate immune activation in the human but not the murine system.
Gesehen am 25.06.2020